SELECTION OF OPTIMAL APPROACHES TO PREVENTION OF NON-COMMUNICABLE DISEASES IN INTERNATIONAL PARTNERSHIP CIRCUMSTANCES - G. Ya. Maslennikova; R. G. Oganov (Кардиоваскулярная терапия и профилактика, 2018)
The growth of social and economical burden of non-communicable diseases (NCD) in all countries around the globe stimulated the national and international institutions for development of political and strategic documents, commitments acception for prevention and control over these diseases. Such commitments, accepted by the countries, are discussed on international meetings of the World Health Organization, the United Nations, the economics of Asia-Pacific collaboration, Northern Dimension countries in the areas of healthcare and social wellbeing. In parallel with these, the professional national and international guidelines are being developed, representing effective populational and individual actions for NCD prevention. Such recommendations are in use in collaboration within projects and programming for economically proven and most efficient actions with further implementation at national levels. Selecting such actions, it is suggested to consider the NCD situation in an exact country, political and economical conditions, materials and technical base, human resources. Special attention is to be paid on selection of target groups for interventions, monitoring standards development and evaluation of efficacy of the joint projects. Main condition for monitoring of NCD situation, their risk factors and assessment of the efficacy programs is an accessible national and global databases that include various parameters of health, that are standardized with the global, regional and national.